Asymmetric Stock Price Responses : Does Inflation or Interest Rate Matter? - Sia, Peck Ching; Puah, Chin Hong; Leong, Choi Meng (2022)
Macroeconomics significantly impacts economic activities and stock market performance given the inextricable link of the stock market to the Indonesian economy. The non-linear autoregressive distributed lags (NARDL) model between 1997 (Q1) and 2021 (Q4) was employed to investigate the asymmetric co-integration of the aforementioned rates by examining the asymmetry inflation model and asymmetry interest rate model. The NARDL specification bounds test implied the existence of co-integration among the study variables. Resultantly, asymmetries existed in the long- and short-run asymmetry interest model but were absent in the inflation counterpart. Under the asymmetry interest rate model, a high interest rate potentially instigates a low stock price while a low interest rate could depress the stock price. Economic developments and exchange rates also demonstrated a positive and significant impact on stock prices in the short run. Examining the implications of multiple asymmetric variables on the stock market proved intriguing as not all macroeconomics variables are globally asymmetric. Notably, the current research supports the presence of an asymmetric influence between interest rates and the stock market in Indonesia. The examination of asymmetry responses to inflation and interest rates in two distinctive models depicted their novel implications on the Indonesian stock market.